A critical review of qualitative research into the experiences of young adults leaving foster care services. Issue 4 (9th December 2014) - Parry, Sarah; Weatherhead, Stephen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Due to the emergence of rich personal narratives within recent research, the purpose of this paper is to review and to explore the experience of transition from care and consider how these accounts can inform care services. Design/methodology/approach – This meta-synthesis follows from several quantitative and mixed method reviews examining how young people experience aging out of the care system. Findings – Three themes emerged from an inductive analysis: navigation and resilience – an interrelated process; the psychological impact of survival; and complex relationship. Research limitations/implications – The findings of a meta-synthesis should not be over generalised and are at least partially influenced by the author's epistemological assumptions (Dixon-Woods et al., 2006). However, a synthesis of this topic has the potential to provide greater insight into how transition can be experienced through the reconceptualising of the personal experiences across the studies reviewed (Erwin et al., 2011). Practical implications – This synthesis discusses the themes; their relationship to existing research and policies, and suggestions for further exploration. The experience of transition is considered critically in terms of its often traumatic nature for the young person aging out of care but also the ways in which the experience itself can build essential resiliencies. Social implications – Reflections for clinical practice are discussed with importance placed upon systemic working, accommodating likely challenges and considering appropriate therapeutic approaches for the client group and their systems. Originality/value – No review thus far has qualitatively examined the narratives told by the young people emerging from care and how these narratives have been interpreted by the researchers who sought them (Hyde and Kammerer, 2009).